Teacher Behavior and Classroom Organization that Fosters Confidence in Children's Relations with Teachers - Ode Yahyu Herliany Yusuf; Maryumi Maryumi; Endri Endri; Harliani Harliani; Erfina Erfina (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this study was to find out how teacher behavior and class organization foster trust in the relationship between children and teachers. This study used qualitative research methods. The research instruments used were observation, interviews, documentation and literacy studies. The results showed that teacher behavior and classroom organization can foster trust in the child-teacher relationship by ensuring continuity of intervention, being consistent and persistent in following up, recognizing teacher observations and insights as valuable, supporting teachers in finding solutions rather than offering instructions, and providing support. emotional and social to change behavior.